Biocontrole de fungos toxigênicos isolados de produto cárneo curado à seco - Martins, Pedro Henrique Alves (2025)
Cured meats are traditional products widely consumed in various cultures, recognized for their complex flavors and economic importance. The production of these foods involves processes such as salting, drying, and fermentation, which promote the development of a complex microbiota, including lactic acid bacteria, yeasts, and filamentous fungi. However, the presence of mycotoxin-producing fungi, especially ochratoxin A (OTA), poses a significant public health risk. The main fungi responsible for contamination in cured meats include Aspergillus westerdijkiae, Penicillium nordicum, and Penicillium verrucosum. This study aimed to investigate the potential of Penicillium nalgiovense, Meyerozyma caribbica, and Hanseniaspora opuntiae as biocontrol agents in inhibiting the growth of toxigenic fungi. Radial inhibition assays were conducted on potato dextrose agar (PDA) and Socol-based agar (SBA), which simulated the initial maturation conditions of meat products. The results demonstrated that P. nalgiovense strains showed the highest efficacy in inhibiting toxigenic fungi at temperatures of 15 °C and 25 °C. OTA quantification was performed using high-performance liquid chromatography with fluorescence detection (HPLC-FLD), revealing significant variation in OTA production among the studied fungi. OTA concentrations ranged from 10.42 µg/kg to 1054.87 µg/kg in PDA and from 5.18 µg/kg to 142.22 µg/kg in SBA, indicating that the composition of the medium influenced mycotoxin production. The findings of this study highlight the relevance of P. nalgiovense as an effective and safe biocontrol agent in cured meat production. Additionally, they emphasize the need to optimize inoculation and maturation conditions to ensure the safety and quality of the final product. Future studies should explore different concentrations and combinations of biocontrol microorganisms, as well as their applications and influences on the sensory characteristics of the product, contributing to the development of effective strategies for mycotoxin control.